Analisis Isi Pesan Dakwah Dalam Buku Pesan Cinta Untuk Kau Dan Aku Karya Aris - Aprilia Nurhasani; Sumaina Duku; Chairunnisah Putri Ayu Ningsih (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2026)
This study aims to analyze the da'wah messages contained in the book Pesan Cinta Untuk Kau dan Aku by Aris. This book is a religious literary work that conveys Islamic values through simple and emotionally engaging language. The research employed a qualitative method with a content analysis approach. Data were collected through documentation techniques by examining the texts in the book and then classified based on the categories of da'wah messages, namely aqidah (faith), sharia (Islamic law), and akhlaq (morality). The findings reveal that the da'wah messages in the book are predominantly related to akhlaq, particularly those concerning love for Allah, compassion toward fellow human beings, and the development of Islamic character in daily life. In addition, the study found aqidah messages emphasizing faith and monotheism, as well as sharia messages encouraging readers to perform religious obligations in accordance with Islamic teachings. Therefore, Pesan Cinta Untuk Kau dan Aku can be considered an effective medium of da'wah, as it successfully communicates Islamic values in a communicative, persuasive, and emotionally engaging manner to its readers.